Technologies to support community-dwelling persons with dementia: a position paper on issues regarding development, usability, effectiveness and cost-effectiveness, deployment, and ethics - Meiland, Franka; Innes, Anthea; Mountain, Gail; Robinson, Louise; Roest, Henriëtte van der; García-Casal, J. Antonio; Gove, Dianne; Thyrian, Jochen René; Evans, Shirley; Dröes, Rose-Marie; Kelly, Fiona; Kurz, Alexander; et al. (JMIR Publications, 2017)
Background: With the expected increase in the numbers of persons with dementia, providing timely, adequate, and affordable care and support is challenging. Assistive and health technologies may be a valuable contribution in dementia care, but new challenges may emerge.